Pengaruh Media Pembelajaran Flash Card Math Terhadap Hasil Belajar Matematika Materi Himpunan Kelas VII - Muslimin Muslimin; Muslimin Tendri; Ichwatun Khasanah (UNION : Jurnal Ilmiah Pendidikan Matematika, 2021)
The purpose of this study was "to find out whether or not there was an effect of the Flash Card Math on the results of learning mathematics in the material set of class VII Palembang State Middle School 7". The subject studied, the seventh-grade students of Palembang State Middle School 7. This type of research is an experiment. Outcomes of students who take part in learning without using the Flash Card Math are 73.13 with 29 students. There is a difference in the average value of mathematics learning outcomes of students using Flash Card Math and the average value of mathematics learning outcomes of students without using Flash Card Math in class VII Palembang Palembang State Middle School 7. The average value of the experimental class is better than the average value of the control class. Based on the analysis of the results of t-test calculations obtained t count = 4.311 for ∝ = 5% and DK = 59 obtained t table = 2.001, this means t count > t table so that H0 is rejected and H1 is accepted. Thus it can be concluded that "there is the influence of Flash Card Math on the mathematics learning outcomes in the set material in class VII Palembang 7 Public Middle School".